Réflexions sur les continuités technologiques : le cas des manuscrits copiés à partir de livres imprimés - Ann Blair (Association Paul Langevin, 2021)
In our time of increasing reliance on digital media the history of the book has a special role to play in studying the codex form and the persistence of old media alongside the growth of new ones. As a contribution to recent work on the continued use of manuscript in the handpress era, I focus on some examples of manuscripts copied from printed books in the Rylands Library and discuss the motivations for making them. Some of these manuscripts were luxury items signalling wealth and prestige, others were made for practical reasons – to own a copy of a book that was hard to buy, or a copy that could be customized in the process of copying. The act of copying itself was also considered to have devotional and/or pedagogical value.